Achieving consensus on the undergraduate curriculum of public health nursing in Turkey - ERGÜN, AYŞE; KADIOĞLU, HASİBE; GÜR, KAMER; EROL, SAİME (WILEY, 2019)
ObjectiveThe aim of this study was to construct a consensus on the undergraduate learning objectives and topics for public health nursing (PHN) in Turkey. DesignA three-round e-mail-based Delphi study was conducted between May and July 2015 with a national sample. SampleNinety-one academics from 54 universities were invited as experts to participate by e-mail. Fifty-nine academics from 43 universities participated in the study. MeasurementsData were analyzed by computing the median, quartiles one and three, and the interquartile range for each learning outcome and topic. Consensus was considered as less than the interquartile range of 1.2. ResultsExperts who participated in the study added 70 learning outcomes, eight main topics, and 278 sub-topics during the first round. Round I generated 170 learning outcomes, 28 main topics, and 385 sub-topics. At the end of Round II, consensus was reached on 126 learning outcomes, 22 main topics and 168 sub-topics. At the end of Round III, consensus was achieved for 126 learning outcomes, 22 main topics, and 169 sub-topics. ConclusionThe learning outcomes and topics that were decided upon through a consensus process will contribute to the standardization and development of PHN education.
Keywords: curriculum planning; delphi technique; education and teaching; nursing education; public health nursing; undergraduate; DELPHI METHOD; EDUCATION; COMPETENCES; TOOL